The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/jim.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Arterial Blood Flow Changes by Orbital Doppler in Chronic Obstructive Pulmonary Disease and Asthma

Abstract: We concluded that retrobulbar hemodynamics change in COPD and asthma is showing 1 of the systemic effects in these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(27 reference statements)
4
4
0
Order By: Relevance
“…Chronic hypoxia and hypercapnia in COPD patients may affect choroidal and retinal blood flow. There are color Doppler ultrasonography studies showing that retrobulbar hemodynamics was impaired, retrobulbar blood flow was reduced, and resistance to blood flow was increased in both retinal and choroidal circulation in COPD patients 22–24 . In parallel with these studies, our study's OCTA results indicated a significant decrease in VD values of SCP and DCP, optic disc, and peripapillary region, especially in the temporal side, and a significant widening in FAZ in the COPD group.…”
Section: Discussionsupporting
confidence: 79%
“…Chronic hypoxia and hypercapnia in COPD patients may affect choroidal and retinal blood flow. There are color Doppler ultrasonography studies showing that retrobulbar hemodynamics was impaired, retrobulbar blood flow was reduced, and resistance to blood flow was increased in both retinal and choroidal circulation in COPD patients 22–24 . In parallel with these studies, our study's OCTA results indicated a significant decrease in VD values of SCP and DCP, optic disc, and peripapillary region, especially in the temporal side, and a significant widening in FAZ in the COPD group.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the EDVs of the arteries did not differ significantly between patients with COPD and control group (Ozer et al 2006). Yakut et al (2015) observed similar findings in 37 patients with COPD, 37 patients with asthma and 41 healthy controls. Resistive index (RI) values of the CRA, temporal PCA and nasal PCA were significantly higher in patients with COPD compared to controls.…”
Section: Coloursupporting
confidence: 65%
“…Yakut et al. () observed similar findings in 37 patients with COPD, 37 patients with asthma and 41 healthy controls. Resistive index (RI) values of the CRA, temporal PCA and nasal PCA were significantly higher in patients with COPD compared to controls.…”
Section: Methodsmentioning
confidence: 68%
See 2 more Smart Citations